Deconstructing Psychedelic Phenomenology: A Thematic Analysis of Discrete Phases of the Psychedelic Experience - H. T. McGovern; L. Bajo; G. Hassed; R. Hoefnagels; M. Levey; N. Rose; A. De Foe; B. T. Hutchinson (Brain and Behavior, 2025)
ABSTRACT The phenomenology of psychedelic experiences has been a long‐standing point of interest to researchers. However, internal experience has been relatively relegated, with much work done on the clinical outcomes of psychedelic therapies. Our reflexive thematic analysis revealed that structurally, people on fora write about their experiences sequentially, considering factors prior to (preparatory), during (acute phase), and after their account of ingesting psychedelics. Themes constructed prior to experience were (1) subjective knowledge and perception of psychedelics, (2) intention and efforts to mentally prepare, and (3) experiential aids. Generated themes during the experience were (1) sensory and cognitive distortions, (2) mindset and affective quality, and (3) environmental stability and support. Experiential impact on behavior and outlook was constructed as the unitary theme following the experience. Future work should look more closely at the role of set and setting within the context of the stages leading up to, during, and after psychedelic administration.